ANALISIS PEMBANGUNAN EKONOMI INDONESIA MENUJU NEGARA MAJU PADA TAHUN 2045 - AdiTriyanto, Sigit; Sanuri, Sanuri; SAmin, Moch (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2022)
The 2024 State Budget (APBN) aims to accelerate inclusive and sustainable economic transformation by increasing productivity and realizing high-value-added economy. To achieve Advanced Indonesia 2045, two main strategies are implemented: short-term and medium-long-term. The short-term focus is to strengthen the economic foundation through controlling inflation, eradicating extreme poverty to 0-1% by 2024, reducing stunting prevalence to 14%, and boosting investment. High economic growth cannot rely solely on household consumption but requires substantial investment. In the medium-long term, the strategy includes addressing gaps in human resources, infrastructure, and institutions. The government focuses on developing superior human resources through education, health, and social protection programs, while also pursuing infrastructure development targets in information technology, energy, and food sectors. Institutional reforms are conducted by improving quality public services and bureaucratic reform. The 2024 APBN prioritizes education, health, social protection, food security, infrastructure, and maintaining legal and security stability. The 2024 APBN also supports the development of the new capital city (IKN), simultaneous elections, reducing stunting prevalence, and improving the welfare of civil servants (ASN), military (TNI), police (Polri), and retirees through salary and pension increases.